Designing Industrial Internship Model to Improve the Skills of Prospective Vocational Teachers - Gunadi; Alias, Maizam; Sofyan, Herminarto; Triyono, Mochammad Bruri (Journal of Technical Education and Training, 2019)
Prospective vocational teachers must have technical expertise in their fields. However, efforts to achieve the competencies of prospective vocational teachers have always lagged behind industries. This is due to the difficulty of teacher training institutions in providing facilities that meets industry standards. Partnership with industry in teacher training is thus, a solution to improve the competency of prospective vocational teachers, both in knowledge, skills and corporate culture. The current industrial attachment practice lacks a mutually beneficial model partnership model. The purpose of this study is to develop a new institution-industry partnership model. The three stage model development methodology was used to guide the model development process. Model development stage was based on findings from field study and literature review. The model validation stage was conducted via focus group discussion with industry players and institutions, and the model implementation stage was conducted with nine automotive authorized dealers in Yogyakarta. At the end, learning four-element internship model was established which includes organizing internship programme, conducting internship, mentoring, and monitoring-evaluation elements. Evaluation of the model indicates that implementation of the model promoting vocational teachers competences via mutually beneficial partnership programme.